Facile fabrication of flexible concave microlens arrays with a well-controlled curvature. (19th August 2021) - Lv, Guowei; Tian, Hongmiao; Shao, Jinyou; Feng, Xuehong; Meng, Lingjie; Ren, Zijun; Yu, Demei
Abstract : Flexible concave microlens arrays with a well-controlled curvature can be fabricated straightforwardly using a leaky dielectric  via  the electrowetting-on-dielectrics phenomenon for potential miniaturized and high-performance flexible optical micro-devices. Abstract : We report the facile fabrication of flexible concave microlens arrays (MLAs) with a well-controlled curvature using a leaky dielectric (LD) via the electrowetting-on-dielectrics (EWOD) phenomenon. MLAs with a larger curvature (up to 0.46 μm −1 ) are fabricated using the LD compared with the perfect dielectric (PD) (∼0.40 μm −1 ). The improved curvature is attributed to the better electrowettability ( i.e., the smaller contact angle) of the LD on the inner-wall of the microhole arrays of the Si-template. Moreover, the curvature of the MLAs can be well controlled by the applied external voltage or the spin rate. Finally, the as-fabricated MLAs show a favorable reflective focusing performance, refractive imaging performance and scattering performance for potential applications in miniaturized and high-performance flexible optical micro-devices.